Incidence and risk factors of kinesiophobia in children following fracture surgery: a prospective cohort study - Xiao, Dan; Li, Lanxing; Lin, Xin; Li, Haisu; Jiang, Xiaoping (Frontiers in Pediatrics, 2025)
ObjectiveKinesiophobia after fracture surgery in pediatric patients may negatively affect recovery. This study aims to investigate the incidence of kinesiophobia and identify associated risk factors in children following fracture surgery.MethodsThis cohort study prospectively enrolled 176 pediatric fracture patients aged 7–15 years who received treatment at a tertiary A-level hospital between November 2023 and June 2024. Data collection included the General Information Questionnaire, Tampa Scale of Kinesiophobia (TSK-11), Pain Rating Scale, and Eysenck Personality Questionnaire (EPQ) to assess demographic characteristics, personality traits, family background, postoperative pain levels, and the incidence of kinesiophobia. Univariate screening through intergroup comparisons was performed, followed by logistic regression analysis to identify independent risk factors for kinesiophobia following fracture surgery in children.ResultsThe incidence of kinesiophobia among school-aged children post-fracture surgery was found to be 59.7% (105/176). Multivariate logistic regression analysis indicated that male gender [2.75 (1.23–6.15), OR (95% CI), p = 0.014], a history of prior fractures [6.62 (1.41–31.12), OR (95% CI), p = 0.017], moderate [4.82 (1.19–19.44), OR (95% CI), p = 0.027] and severe [5.14 (1.13–23.37), OR (95% CI), p = 0.034] postoperative pain, and a personality trait inclination towards neuroticism [1.12 (1.04–1.22), OR (95% CI), p = 0.004] were significant factors contributing to the development of kinesiophobia after surgery.ConclusionThe incidence of kinesiophobia is relatively high among school-aged children following fracture surgery. Healthcare providers should promptly identify cases of kinesiophobia and develop targeted care strategies based on identified risk factors to reduce its occurrence.